Arab Republic of Egypt - Reshaping Egypt's Economic Geography : Domestic Integration as a Development Platform, Volume 1 - World Bank (Washington, DC, 2012)
This report investigates Egypt's regional economic growth, explores the causes for geographically unbalanced development, and proposes policy options to make unbalanced growth compatible with inclusive development. In Egypt, despite rapid progress in most welfare indicators in lagging regions, there are still substantial gaps in consumption and opportunities between growth poles and the rest of the country. This report's central proposal is adopting spatial integration as a development platform, in which the policy focus shifts from spreading out industrial location to spreading out access to basic public services and facilitating factor mobility, which will make growth more inclusive and development more balanced in Egypt. Egypt's new political environment provides an opportunity to examine this perennial problem from a new perspective. Adopting integration as a development platform is not simple because spatial disparities are spanned in three dimensions: urban/rural dichotomies, the upper Egypt/lower Egypt duality, and the differences between large metropolises and the rest of the country. This report first identifies the gaps in consumption and in opportunities, showing the stark contrasts between regions and how they evolve through time. It then explores the causes of the gaps, revealing a multiplicity of factors and exposing the complexity of the problem. Finally, the bulk of the report presents the policy options to address the integration challenges.